Hollywood's Global Expansion and Racialized Film Industry. Issue 1 (February 2020) - Kim, Minjeong; Brunn-Bevel, Rachelle J.
A theory on the political economy of image production argues that the U.S. film industry, namely, Hollywood, prioritizes financial considerations over racial justice or political correctness. Decisions made in the production and marketing processes are to minimize financial risks, but they often limit the representation of racial–ethnic minority filmmakers and actors. At the same time, Hollywood incorporates foreign-born directors and actors to reach international audiences. This article assesses how Hollywood's "going global" impacts local racial–ethnic minority politics in the U.S. film business. As a part of a larger study examining the 100 top-grossing films in the United States from 1995 to 2014, we closely examine films where racial–ethnic minorities comprise the majority of the cast or films where minorities are the lead actors. We argue that the incorporation of foreign-born directors and actors undermines U.S. racial–ethnic minority filmmakers' efforts to tell cinematic narratives from a critical perspective. Also, Hollywood fails to promote black films and black actors based on the assumption that they cannot appeal to international audiences, but our findings illustrate that black films directed by black directors perform well domestically and they show great potential with more support from Hollywood.